Editorial [ Hot Topic: Drugs Targets in Parkinson's Disease:Where Are We and Where should We Go? (Guest Editor: Mark R. Cookson)] - R. Cookson, Mark (CNS & Neurological Disorders - Drug Targets, 2011)
As a relatively common neurodegenerative disease associated with aging, Parkinson's disease (PD) impacts increasing numbers of people as population structures are shifted towards older individuals. For many people living with PD, the disease process leads progressively to increased disability and lowered quality of life. Many of the cardinal symptoms in PD relate to impairment of normal fluid movement, but as the disease progresses more of the brain is involved such that at the later stages it is not uncommon for higher cortical functions to be damaged. Overall, this makes treating PD a complex issue but an important one for people living with the disease and for their caregivers and families. The articles collected in this special edition of CNS & Neurolgical Disorders - Drug Targets generally address two different issues that relate to the treatment of PD. The first is the current status of symptomatic treatments. Many, but not all, of the movement problems in PD are well treated in the early stages of the disease, most famously with the use of L-DOPA, the precursor for the neurotransmitter dopamine. For many patients, L-DOPA is effective, safe and restores movement for several years although it does not address all the neurological symptoms in PD and can become less effective over time and has some side effects such as dyskinesia. L-DOPA is not covered in this volume as it has been addressed in depth in many previous reviews and monographs, but treatments based around other neurotransmitter systems or using nonpharmacological approaches are discussed. It is critical to keep developing treatments for the variety of symptoms in PD, to provide a better armamentarium for clinicians and to find ways to maintain benefit while minimizing side effects. To the latter end, treating the side effects themselves is also important, as shown in this volume by the discussion of the basic biology of dyskinesias and identification of new ways to address this problem. But, there is a second issue that will be addressed in this volume, and that is how to treat the underlying disease process as well as the symptoms. Ideally, we would like to halt or even reverse the progressive nature of PD perhaps at the stage of mild, tolerable movement problems, which again underscores the need for improved symptomatic treatments. Treating the underlying progressive pathophysiology is difficult in most neurodegenerative conditions and such disease modifying-therapies remain an unmet ideal for drug development. But, there are several ways in which we could think about drug targets where the promise of modifying the disease could one day be met. Those relate to better understanding of the underlying causes of PD. One of the recent revolutions in thinking about PD, and many other neurodegenerative diseases, has come from the recognition that genetics explains at least some of the lifetime risk of disease in families but also in apparently sporadic disease. It follows, therefore, that understanding the molecules that contribute to genetic risk of disease might lead us to a better understanding of disease process and hence to new targets for modifying disease and this will be discussed in some of the collected articles here. Also, understanding the basic biology of the nervous system can be used to identify neuroprotective pathways, and the possibility of using trophic factors to treat PD is also covered in this collection....